THE IMPACT OF ANXIETY AND STRESS ON ACADEMIC PERFORMANCE: A GLOBAL AND UZBEK PERSPECTIVE (International conference on multidisciplinary science, 2024)
This article explores the impact of anxiety and stress on academic performance, focusing on both global and Uzbek perspectives. Anxiety and stress, common psychological responses to academic pressure, can negatively influence cognitive functioning, impairing attention, memory, and problem-solving abilities, thus leading to decreased academic achievement. While moderate levels of stress may enhance performance, excessive anxiety often results in poor academic outcomes. The article examines factors contributing to academic anxiety, including test anxiety, perfectionism, and external expectations, particularly within the context of Uzbekistan’s highly competitive education system. It also discusses coping strategies such as cognitive-behavioral therapy (CBT), mindfulness practices, and institutional reforms aimed at mitigating the effects of stress and anxiety on students. The research concludes that addressing psychological well-being is essential to fostering more effective learning environments and improving student performance in Uzbekistan and beyond.